2012
DOI: 10.1523/jneurosci.2901-11.2012
|View full text |Cite
|
Sign up to set email alerts
|

RAE-1, a Novel PHR Binding Protein, Is Required for Axon Termination and Synapse Formation inCaenorhabditis elegans

Abstract: Previous studies in C. elegans showed that RPM-1 (Regulator of Presynaptic Morphology-1) regulates axon termination and synapse formation. In order to understand the mechanism of how rpm-1 functions, we have used mass spectrometry to identify RPM-1 binding proteins, and have identified RAE-1 (RNA Export protein-1) as an evolutionarily conserved binding partner. We define a RAE-1 binding region in RPM-1, and show that this binding interaction is conserved and also occurs between Rae1 and the human ortholog of R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
60
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(66 citation statements)
references
References 26 publications
6
60
0
Order By: Relevance
“…Thus, although RAE-1 and FSN-1 are likely to be in close physical proximity, FSN-1 is unlikely to act as an adaptor for recruitment of RAE-1 into RPM-1 protein complexes and vice versa. Our biochemical results are consistent with prior genetic and proteomic results, which showed that RAE-1 is not a target of RPM-1 ubiquitin ligase activity (28,33).…”
Section: Rip An In Vivo Inhibitor Of the Rpm-1⅐fsn-1 Ubiquitinsupporting
confidence: 92%
See 4 more Smart Citations
“…Thus, although RAE-1 and FSN-1 are likely to be in close physical proximity, FSN-1 is unlikely to act as an adaptor for recruitment of RAE-1 into RPM-1 protein complexes and vice versa. Our biochemical results are consistent with prior genetic and proteomic results, which showed that RAE-1 is not a target of RPM-1 ubiquitin ligase activity (28,33).…”
Section: Rip An In Vivo Inhibitor Of the Rpm-1⅐fsn-1 Ubiquitinsupporting
confidence: 92%
“…Note that FLAG-FSN-1 coprecipitated exclusively with domain 5 of RPM-1 (GFP-D5) (top panel). Consistent with a previous study, FLAG-RAE-1 also coprecipitated with GFP-RPM-1 domain 5 (GFP-D5) (top panel, last lane) (28). Shown are representatives of experiments that were independently performed at least three times.…”
Section: A Single Domain In Rpm-1 Is Sufficient For Binding To Fsn-1-supporting
confidence: 87%
See 3 more Smart Citations